Aging and the social sciences - Binstock, Robert H; George, Linda K (San Diego, 2001)
Includes bibliographical references and index.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Gerontology; Aging -- Social aspects.; Life change events in old age.; Older people -- Care.; Aged.; Aging.; Life Change Events -- Aged.; Social Sciences; Nghiên cứu tuổi già; Khoa học xã hội